Tax Administration Transformation through The Implementation of Coretax DJP in 2025 - Judijanto, Loso; Arum, Mega; Kaswoto, Junet (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study analyzes the transformation of tax administration through the implementation of the Core Tax Administration System (Coretax DJP) in Indonesia in 2025. The reform aims to integrate tax administration processes, improve service quality, and enhance administrative efficiency through digital transformation aligned with modern public sector governance. A quantitative research approach was employed using primary data collected from 125 community respondents who interact with tax administration services. Data were gathered through a structured questionnaire measured on a Likert scale and analyzed using SPSS version 25. Descriptive and inferential statistical analyses were conducted to examine perceptions of efficiency, ease of use, service quality, transparency, and overall satisfaction with Coretax DJP as a digital tax platform. The results indicate that the implementation of Coretax DJP has a positive and significant impact on tax administration transformation by simplifying processes and improving user experience. Perceived efficiency, service quality, ease of use, and transparency significantly influence overall user satisfaction, with efficiency emerging as the most dominant factor affecting public perceptions. The integrated digital system enables faster processing, better data management, and improved communication between taxpayers and tax authorities, contributing to increased trust in tax services. These findings provide empirical evidence that digital tax system integration can strengthen public sector performance and taxpayer engagement, while also highlighting the importance of continuous system refinement, digital literacy support, and responsive service mechanisms to ensure the sustainability and long-term effectiveness of tax administration reforms in Indonesia.